Preparation method of solid electrolyte membrane

By performing crushing, sieving, dissolving, refining and rolling treatment of solid electrolyte raw materials, the problem of electrolyte membrane preparation in solid battery is solved, and high-performance and stable solid electrolyte membrane preparation is achieved, with industrial application potential.

CN119447436APending Publication Date: 2025-02-14GTC-POWER ZHUHAI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411603709.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing research on solid-state batteries is mainly limited by the difficulties in preparing solid-state electrolyte membranes, especially in the challenge of achieving large-scale continuous preparation and improving the performance and stability of electrolyte membranes.

Method used

The electrolyte raw materials are processed by crushing and sieving to form electrolyte particles, and then dissolved in a solvent, and then stirred and dried to form a fine powder. Finally, a solid electrolyte membrane is prepared by rolling processing.

Benefits of technology

This method simplifies the preparation process, reduces production costs, increases the density and physical strength of the electrolyte membrane, ensures its ion conduction performance and stability, is suitable for battery-end applications, and has industrial application potential.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a solid electrolyte membrane. The preparation method of the solid electrolyte membrane comprises the following steps: crushing and screening electrolyte raw materials to obtain electrolyte particles; dissolving the electrolyte particles into a solvent, and uniformly mixing to obtain electrolyte slurry; carrying out refining treatment on the electrolyte slurry to obtain refined powder; and carrying out rolling treatment on the refined powder to obtain the solid electrolyte membrane. According to the preparation method of the solid electrolyte membrane, the preparation process is simplified, the production cost is reduced, and the production efficiency is improved. The electrolyte slurry is refined by optimizing the process conditions for preparing the electrolyte powder, so that the ionic conduction performance and the stability of the electrolyte membrane are ensured; and meanwhile, the preparation process is green and environment-friendly and has huge industrial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid-state batteries, and specifically discloses a method for preparing a solid-state electrolyte membrane. Background Art

[0002] With the rapid development of portable electronic devices and electric vehicles, the demand for high-performance batteries is growing. Although traditional lithium-ion batteries have made significant progress in energy density and cycle life, they still have some limitations, such as safety issues, poor thermal stability, and limited energy density. The mainstream battery technology on the market currently uses liquid electrolytes. Although they have high energy density, liquid electrolytes have the risk of leakage and may cause fire or explosion when overheated or mechanically damaged.

[0003] In order to improve safety and energy density, solid-state battery technology came into being. Solid-state batteries use solid electrolytes instead of liquid electrolytes, which can reduce the volume and weight of the battery while improving its thermal stability and safety.

[0004] Solid-state batteries have broad application prospects in new energy and microelectronics fields such as electric vehicles and wearable devices. However, the existing research on solid-state batteries is still in the laboratory research and development stage. The main limitation is that the core components of solid-state batteries are difficult to achieve large-scale continuous preparation. As the core component of all-solid-state batteries, solid electrolytes need to have high ionic conductivity and excellent stability. However, at present, in solid-state batteries with soft-pack cells as the main application form, the preparation of electrolyte membranes still faces many challenges. In addition, unlike traditional lithium-ion batteries, the electrolyte has fluidity and can fully infiltrate the electrodes, thereby ensuring ion transfer during the cycle. The inorganic solid electrolyte membrane needs to have a certain flexibility to ensure sufficient contact between the electrode / electrolyte layer, thereby improving the performance of all-solid-state batteries.

[0005] Therefore, the preparation of electrolyte membrane is the key to the practical application of all-solid-state batteries, and it is also the key to the transition of all-solid-state batteries from the laboratory stage to the industrial production stage. Summary of the invention

[0006] In order to solve the above technical problems, the present application provides a method for preparing a solid electrolyte membrane, aiming to simplify the preparation process, reduce production costs, and improve the performance and stability of the electrolyte membrane to meet the demand for solid electrolyte membranes in the new energy field.

[0007] The present application provides a method for preparing a solid electrolyte membrane, which adopts the following technical solution: A method for preparing a solid electrolyte membrane, comprising crushing and screening electrolyte raw materials to obtain electrolyte particles; Dissolving the electrolyte particles in a solvent and mixing them evenly to obtain an electrolyte slurry; The electrolyte slurry is refined to obtain a refined powder; The refined powder is subjected to roller pressing to obtain the solid electrolyte membrane.

[0008] In some embodiments, during the process of dissolving the electrolyte particles into the solvent, the stirring speed ranges from 100 rpm to 2000 rpm; preferably, it is 500 rpm.

[0009] In some embodiments, the electrolyte raw material is one or more of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte.

[0010] In some embodiments, the sulfide solid electrolyte is Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11−x M 2−x P 1+x S 12 (M = Ge, Sn, Si) one or more; The oxide solid electrolyte is selected from garnet ceramic oxide solid electrolyte Li 6.5 Ln3Z 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 , Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 , Li 14 Zn(GeO4)4、Li 3+x (P 1-x Si x )O4(where 0 <x<1)、Li 3+x Gex V 1-x O4 (where 0 < x < 1), LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr or La; The halide electrolyte LiaMbXc, where M is a metal element, including one or more elements of Sc, Y, La, Ho, Er, Tm, Yb, Lu, Al, Ga, In, Tl, Fe; X is a non - metal element selected from one or more of F, Cl, Br, I, At, O, S, Se, Te; 0 < a ≤ 5, 0 < b ≤ 3, 0 < c ≤ 10.

[0011] In some embodiments, the oxide solid electrolyte is preferably Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x T i2-x (PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x (PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LiT i2 (PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3 or LiHf2(PO4)3, Li 0.33 La 0.55 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x-y Sr 1-x TayZr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25); The halide electrolyte is preferably Li3ScCl6, Li2Sc 2 / 3 Cl4, Li2In 1 / 3 Sc 1 / 3 Cl4, Li 2.25 Zr 0.75 Fe 0.25Cl6、Li 2.7 Zr 0.3 In 0.7 One or more of Cl6, Li2ZrCl6, Li2ZrBr6, Li3InCl6, Li3InBr6.

[0012] In some embodiments, the particle size of the electrolyte particles is 1 μm-20 μm. Preferably, the particle size of the electrolyte particles is 6 μm.

[0013] In some embodiments, the solvent is selected from one or more of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isoamyl ether, butyl butyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate.

[0014] In some embodiments, the refinement process specifically includes the following steps: The electrolyte slurry is subjected to ultrasonic stirring treatment to depolymerize the electrolyte particles, and the depolymerized electrolyte particles are dried to obtain a dry electrolyte powder, wherein the drying temperature is 50° C.-200° C.; preferably, the drying temperature is 80° C.; Mix the dried electrolyte powder with the binder, control the mixer speed to 10 rpm-5000 rpm, preferably, the speed is 150 rpm, and the mixing time is controlled to 5 min-60 min; The speed of the mixer is adjusted so that the binder is fiberized under the shear force of the mixer blade to form a bonding network. The mixer speed is 10 rpm-5000 rpm; preferably, the speed is 4000 rpm; the running time is 5 min-60 min; preferably, the fiberization time is 10 min to obtain a fiberized mixture; The fiberized mixture is granulated, the mixer speed is 10rpm-5000rpm; preferably, the speed is 1500rpm; the running time is 5min-60min; preferably, the running time is 30min to obtain a refined powder.

[0015] In some embodiments, the roller pressing process specifically comprises the following steps: The refined powder is placed in a roller pressing device, and the differential speed ratio between the rollers in the roller pressing device is adjusted to 1:1.1-1:5, preferably, the differential speed ratio is 1:2; the spacing between the rollers is set in a decreasing manner, and the roller spacing ratio ranges from 5:1-1.1:1; preferably, the roller spacing ratio is 2:1; wherein the temperature range of the rollers in the roller pressing device is 10°C-200°C, preferably, the roller temperature is 80°C.

[0016] In summary, this application has the following beneficial effects: The preparation method of the solid electrolyte membrane of the present invention simplifies the preparation process, reduces production costs, and improves production efficiency. By optimizing the process conditions for preparing electrolyte powder, the electrolyte slurry is refined, the uniformity and particle size of the electrolyte particles are ensured by crushing and screening, and the particles are further refined by combining wet refinement, so that the electrolyte membrane after dry rolling has good density and physical strength, and the ion conductivity and stability of the electrolyte membrane are ensured, and it can be well applied to the battery end and has excellent performance; compared with dry rolling, the preparation method in this application can effectively reduce the gap inside the electrolyte membrane through a two-step refinement process, improve the density, and then reduce the thickness of the electrolyte membrane. At the same time, the preparation process is green and environmentally friendly, and has great potential for industrial application. DETAILED DESCRIPTION

[0017] The following description provides specific application scenarios and requirements of the present application, with the purpose of enabling those skilled in the art to make and use the content in the present application. It will be apparent to those skilled in the art that various local modifications to the disclosed embodiments are apparent, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present application. Therefore, the present application is not limited to the embodiments shown, but to the widest scope consistent with the claims.

[0018] The present application provides a method for preparing a solid electrolyte membrane, comprising: The electrolyte raw materials are crushed and sieved to obtain electrolyte particles; Dissolving electrolyte particles in a solvent and mixing them evenly to obtain an electrolyte slurry; The electrolyte slurry is refined to obtain a refined powder; Rolling the refined powder to obtain the solid electrolyte membrane; In some embodiments, the refinement process specifically includes the following steps: The electrolyte slurry is subjected to ultrasonic stirring treatment to depolymerize the electrolyte particles, and the depolymerized electrolyte particles are dried to obtain a dry electrolyte powder, wherein the drying temperature is 50° C.-200° C.; preferably, the drying temperature is 80° C.; Mix the dried electrolyte powder with the binder, control the mixer speed to 10 rpm-5000 rpm, preferably, the speed is 150 rpm, and the mixing time is controlled to 5 min-60 min; The speed of the mixer is adjusted so that the binder is fiberized under the shear force of the mixer blade to form a bonding network. The mixer speed is 10 rpm-5000 rpm; preferably, the speed is 4000 rpm; the running time is 5 min-60 min; preferably, the fiberization time is 10 min to obtain a fiberized mixture; The fiberized mixture is granulated, the mixer speed is 10rpm-5000rpm; preferably, the speed is 1500rpm; the running time is 5min-60min; preferably, the running time is 30min to obtain a refined powder.

[0019] In some embodiments, the roller pressing process specifically comprises the following steps: The refined powder is placed in a roller pressing device, and the differential speed ratio between the rollers in the roller pressing device is adjusted to 1:1.1-1:5, preferably, the differential speed ratio is 1:2; the spacing between the rollers is set in a decreasing manner, and the roller spacing ratio ranges from 5:1-1.1:1; preferably, the roller spacing ratio is 2:1; wherein the temperature range of the rollers in the roller pressing device is 10°C-200°C, preferably, the roller temperature is 80°C.

[0020] In some embodiments, during the process of dissolving the electrolyte particles into the solvent, the stirring speed ranges from 100 rpm to 2000 rpm; preferably, it is 500 rpm.

[0021] In some embodiments, the electrolyte raw material is one or more of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte.

[0022] In some embodiments, the sulfide solid electrolyte is Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11−x M 2−x P 1+x S 12 (M = Ge, Sn, Si) one or more; The oxide solid electrolyte is selected from garnet ceramic oxide solid electrolyte Li 6.5 Ln3Z 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb0.25 O 12 、Li 6.25 Al 0.25 La3Zr2O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 、Li 14 Zn(GeO4)4、Li 3+x (P 1-x Si x )O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1), LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, or La; The halide electrolyte LiaMbXc, where M is a metal element, including one or more elements selected from Sc, Y, La, Ho, Er, Tm, Yb, Lu, Al, Ga, In, Tl, Fe; X is a non-metal element, one or more of F, Cl, Br, I, At, O, S, Se, Te; 0 < a ≤ 5, 0 < b ≤ 3, 0 < c ≤ 10.

[0023] In some embodiments, the oxide solid electrolyte is preferably Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x T i2-x (PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x (PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LiT i2 (PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3 or LiHf2(PO4)3, Li 0.33 La 0.55 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x-y Sr1-x TayZr 1-y O3 (where x = 0.75y and 0.60 <y<0.75)、Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3、Li 3x La (2 / 3-x) TiO3 (of which 0 <x<0.25); The halide electrolyte is preferably Li3ScCl6, Li2Sc 2 / 3 Cl4、Li2In 1 / 3 Sc 1 / 3 Cl4、Li 2.25 Zr 0.75 Fe 0.25 Cl6、Li 2.7 Zr 0.3 In 0.7 One or more of Cl6, Li2ZrCl6, Li2ZrBr6, Li3InCl6, Li3InBr6.

[0024] In some embodiments, the particle size of the electrolyte particles is 1 μm-20 μm. Preferably, the particle size of the electrolyte particles is 6 μm.

[0025] In some embodiments, the solvent is selected from one or more of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isoamyl ether, butyl butyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate. The present application is further described in detail below with reference to the embodiments. Example

[0026] A method for preparing a solid electrolyte membrane comprises: Step 1: Prepare electrolyte raw materials (Li7P3S 11 ) is crushed and screened, wherein the electrolyte particles obtained have a particle size of 6 μm; Step 2, dissolving the electrolyte particles in toluene solvent, and mixing them evenly to obtain electrolyte slurry; wherein the stirring speed is 500 rpm; Step 3, subjecting the electrolyte slurry to ultrasonic stirring treatment to depolymerize the electrolyte particles, and drying the depolymerized electrolyte particles to obtain dry electrolyte powder, wherein the drying temperature is 80° C.; The dried electrolyte powder was mixed with polytetrafluoroethylene, the mixer speed was controlled to 150 rpm, and the mixing time was controlled to 15 min; The speed of the mixer is adjusted so that the binder is fiberized under the shear force of the mixer blade, thereby forming a bonding network. The mixer speed is 4000 rpm. The fiberization time is 10 min to obtain a fiberized mixture. The fiberized mixture was granulated at a mixer speed of 1500 rpm and the operation time was 30 min to obtain a fine powder; Step 4: Place the refined powder in a roller pressing device, adjust the differential speed ratio between the rollers in the roller pressing device to 1:2; the roller spacing is set to decrease, and the roller spacing ratio is 2:1; the temperature of the rollers in the roller pressing device is 80°C The electrolyte membrane prepared through the above steps can be as thin as 80μm, with uniform thickness and an error of ±1μm, an ionic conductivity of 3mS / cm, and a certain degree of flexibility. Example

[0027] The specific preparation steps of the solid electrolyte membrane in Example 2 are the same as those in Example 1, except that the temperature of the roller in Example 2 is 100°C.

[0028] The electrolyte membrane prepared through the above steps can be as thin as 80μm with an error of ±1μm, an ion conductivity of 3mS / cm, and has a certain flexibility.

[0029] Comparative Example 1 provides a method for preparing a solid electrolyte membrane, which is prepared by pressing electrolyte powder in a mold and then demolding it using a manual tablet press.

[0030] The manual tablet press pressure was 360 MPa; the holding time was 3 min, and the rest was the same as in Example 1.

[0031] The thickness of the electrolyte sheet is 500μm. The conductivity of the electrolyte layer after demolding after cold pressing is 3.5mS / cm, and the thickness is relatively thick, which is not conducive to the energy density of the battery cell. In addition, small-area tablets can be demolded smoothly, but large-area powder tablets will crack after demolding.

[0032] The specific preparation steps of the solid electrolyte membrane in Comparative Example 2 are the same as those in Example 1, except that the electrolyte membrane molding and thinning steps in Comparative Example 2 are prepared by manual calendering on a heating table.

[0033] The heating temperature of the heating table is 80°C; The electrolyte membrane prepared through the above steps can be as thin as 150μm with an error of ±5μm, an ion conductivity of 2mS / cm, and has a certain flexibility.

[0034] The specific preparation steps of the solid electrolyte membrane in Comparative Example 3 are the same as those in Example 1, except that the electrolyte slurry in Comparative Example 3 is not subjected to refinement treatment, the rollers in the rolling process are not heated, and the electrolyte membrane is not subjected to a thinning step.

[0035] The electrolyte membrane prepared through the above steps can be as thin as 120μm with an error of ±1μm, an ionic conductivity of 2.7mS / cm, and has a certain flexibility.

[0036] It can be seen from the results of Example 1 and Comparative Example 1 that in order to achieve large-scale, large-area, and continuous molding of the electrolyte membrane, a certain amount of binder needs to be added to support its physical structural integrity.

[0037] It can be seen from the results of Example 1 and Comparative Example 2 that manual molding takes a long time and has poor precision control, and the thickness of the electrolyte membrane is also thick, which is not conducive to improving the energy density of the battery cell. In addition, the difference in ionic conductivity also shows that the binder is unevenly distributed during manual molding. We reasonably infer that through the two-step refinement in this application (raw material crushing, screening and wet refinement can effectively ensure the uniformity and particle size of the electrolyte particles, so that the electrolyte membrane has good density and physical strength, and ensures the ion conductivity and stability of the electrolyte membrane; compared with dry rolling, the preparation method in this application can effectively reduce the voids inside the electrolyte membrane through a two-step refinement process, improve the density, and then reduce the thickness of the electrolyte membrane, so the thickness of the electrolyte membrane in Comparative Example 2 is much higher than the thickness of the electrolyte membrane in Example 1).

[0038] The results of Example 1, Comparative Example 3 and Example 2 show that 80°C is the optimal roller temperature. Low-temperature rollers are not conducive to electrolyte membrane molding and secondary dispersion of binders. High-temperature rollers consume a lot of energy, the improvement effect is not obvious and there are certain operational risks.

[0039] It should be noted that different embodiments may produce different beneficial effects. In different embodiments, the beneficial effects that may be produced may be any one or a combination of the above, or any other possible beneficial effects.

[0040] The basic concepts have been described above. Obviously, for those skilled in the art, the above detailed disclosure is only for example and does not constitute a limitation of this specification. Although not explicitly stated here, those skilled in the art may make various modifications, improvements and corrections to this application. Such modifications, improvements and corrections are suggested in this specification, so such modifications, improvements and corrections still belong to the spirit and scope of the exemplary embodiments of this application.

[0041] In addition, when terms such as "first", "second", and "third" are used in the specification of this application to describe various features, these terms are only used to distinguish these features and cannot be understood as indicating or implying the relationship between the features, the relative importance, or implicitly indicating the number of features indicated.

[0042] At the same time, the present application uses specific words to describe the embodiments of this specification. For example, "one embodiment", "an embodiment", and / or "some embodiments" refer to a certain feature, structure or characteristic related to at least one embodiment of the present application. Therefore, it should be emphasized and noted that "one embodiment" or "an embodiment" or "an alternative embodiment" mentioned twice or more in different positions in the present application does not necessarily refer to the same embodiment. In addition, some features, structures or characteristics in one or more embodiments of the present application can be appropriately combined.

[0043] Similarly, it should be noted that in order to simplify the description of the disclosure of this application and thus help understand one or more embodiments of the invention, in the above description of the embodiments of this application, multiple features are sometimes combined into one embodiment and its description. However, this disclosure method does not mean that the features required by the object of this application are more than the features mentioned in the claims. In fact, the features of the embodiments are less than all the features of the single embodiment disclosed above.

[0044] Finally, it should be understood that the embodiments described in this application are only used to illustrate the principles of the embodiments of the present application. Other variations may also fall within the scope of the present application. Therefore, as an example and not a limitation, the alternative configurations of the embodiments of the present application may be considered to be consistent with the teachings of the present application. Accordingly, the embodiments of the present application are not limited to the embodiments explicitly introduced and described in the present application.

Claims

1. A method for preparing a solid electrolyte membrane, characterized in that: include: The electrolyte raw materials are crushed and sieved to obtain electrolyte particles; Dissolving electrolyte particles in a solvent and mixing them evenly to obtain an electrolyte slurry; The electrolyte slurry is refined and dried to obtain a refined powder; The refined powder is mixed with a binder and subjected to a roller pressing process to obtain the solid electrolyte membrane.

2. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The electrolyte raw material is one or more of a sulfide solid electrolyte, an oxide solid electrolyte and a halide solid electrolyte.

3. The method for preparing a solid electrolyte membrane according to claim 2, characterized in that: The sulfide solid electrolyte is Li7P3S 11 , Li3PS4, Li6PS5X (X=Cl, Br, I), Li 11−x M 2−x P 1+x S 12 (M = Ge, Sn, Si) one or more; The oxide solid electrolyte is selected from garnet ceramic oxide solid electrolytes Li 6.5 La3Zr 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 、Li 6.2 Ga 0.3 La 2.95 Rb 0.05 Zr2O 12 、Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 、Li 6.25 Al 0.25 La3Zr2O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 、Li 14 Zn(GeO4)4、Li 3+x (P 1-x Si x )O4(where 0 < x < 1), Li 3+x Ge x V 1-x O4(where 0 < x < 1), LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr or La; The halide electrolyte LiaMbXc, wherein M is a metal element, including one or more elements of Sc, Y, La, Ho, Er, Tm, Yb, Lu, Al, Ga, In, Tl, Fe; X is one or more non-metallic elements of F, Cl, Br, I, At, O, S, Se, Te; 0<a≤5, 0<b≤3, 0<c≤10.

4. The method for preparing a solid electrolyte membrane according to claim 3, characterized in that: The oxide solid electrolyte is preferably Li 1+x Al x Ge 2-x (PO4)3(LAGP)(where 0≤x≤2), Li 1+x Al x T i2-x (PO4)3(LATP)(where 0≤x≤2), Li 1+x Y x Zr 2-x (PO4)3(LYZP)(where 0≤x≤2), Li 1.3 Al 0.3 Ti 1.7 (PO4)3、LiT i2 (PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3 or LiHf2(PO4)3, Li 0.33 La 0.55 TiO3、LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x-y Sr 1- x TayZr 1-y O3 (where x = 0.75y and 0.60 <y<0.75)、Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3、Li 3x La (2 / 3-x) TiO3 (of which 0 <x<0.25); The halide electrolyte is preferably Li3ScCl6, Li2Sc 2 / 3 Cl4、Li2In 1 / 3 Sc 1 / 3 Cl4、Li 2.25 Zr 0.75 Fe 0.25 Cl6、Li 2.7 Zr 0.3 In 0.7 One or more of Cl6, Li2ZrCl6, Li2ZrBr6, Li3InCl6, Li3InBr6.

5. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The particle size of the electrolyte particles is 1 μm-20 μm.

6. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The solvent is selected from one or more of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, dimethyl ether, dibutyl ether, 1,2-ethylenediamine, dichloroethane, dibromomethane, anisole, triethyl phosphate, dimethyl sulfoxide, dichloromethane, 1,2-ethanedithiol, isoamyl ether, butyl butyrate, isopropyl ether, n-heptane, hexene, ethyl acetate or benzyl acetate.

7. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The refinement process specifically comprises the following steps: The electrolyte slurry is subjected to ultrasonic stirring treatment to depolymerize the electrolyte particles, and the depolymerized electrolyte particles are dried to obtain a dry electrolyte powder, wherein the drying temperature is 50° C.-200° C.; The dried electrolyte powder is mixed with the binder, the mixer speed is controlled to be 10 rpm-5000 rpm, the mixing time is controlled to be 5 min-60 min, a fiberized mixture is obtained and granulated to obtain a refined powder.

8. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The roller pressing process specifically comprises the following steps: The refined powder is placed in a roller pressing device, and the differential speed ratio between the rollers in the roller pressing device is adjusted to 1:1.1-1:5, the spacing between the rollers is set in a decreasing manner, and the roller spacing ratio ranges from 5:1 to 1.1:1; wherein the temperature range of the rollers in the roller pressing device is 10°C-200°C.